The Segovia: its origin to its scene of looting and bloody struggles (Raíces: Revista de Ciencias Sociales y Políticas, 2019)
It is not a complete story, it is just small sketches but with interesting strokes of what is our history that will surely arouse the interest of knowing a little more about this Segovian terroir as they are called by those who have approached it as they are approached by those we would like to arrive at the hands of all Segovians from inside and outside the Republic, because we do not doubt that they will be interested in knowing something about the past of this part of the land that saw them born, and that they will undoubtedly love, with a greater, if not equal, love from whom He has spent long vigils to make known to others what he longed to know in the years of his childhood; hoping that others better prepared will perfect the work. Nueva Segovia is a whole mountainous area, with various natural attractions, among which there are large hills This department is located in one of the northern ends of the country and enjoys a pleasant cool climate, saturated with a charming landscape and a fertile soil, this region is conducive to the farmer so much that, intoning a song of hope, fertilizes the groove of a grateful land. Its small towns and villages are characterized by their quiet atmosphere and the central adobe houses with tile roofs; In some of them there are craft workshops that produce interesting decorative pieces. Nueva Segovia is not only the redoubt of a parenthesis of the conquest in Nicaraoan lands, it is a land of customs and traditions.
Keywords: Segovias; reductions; Nueva Segovia; its history and bloody struggles